Conductance of a tunnel point contact of noble metals in the presence of a single defect: Электpонные свойства металлов и сплавов - Avotina, Ye.S.; Kolesnichenko, Yu.A.; Roobol, S.B.; Ruitenbeek, J.M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
In paper (Avotina et.al., Phys. Rev. B74, 085411 (2006)) the effect of Fermi surface anisotropy to the conductance of a tunnel point contact, in the vicinity of which a single point-like defect is situated, has been investigated theoretically. The oscillatory dependence of the conductance on the distance between the contact and the defect has been found for a general Fermi surface geometry. In this paper we apply the method developed in (Avotina et.al., Phys. Rev. B74, 085411 (2006)) to the calculation of the conductance of noble metal contacts. An original algorithm, which enables the computation of the conductance for any parametrically given Fermi surface, is proposed. On this basis a pattern of the conductance oscillations, which can be observed by the method of scanning tunneling microscopy, is obtained for different orientations of the surface for the noble metals.